1997
DOI: 10.1109/4233.654859
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of sensitivity of breast cancer diagnosis with adaptive neighborhood contrast enhancement of mammograms

Abstract: Mammograms are difficult to interpret, especially of cancers at their early stages. In this paper, we analyze the effectiveness of our adaptive neighborhood contrast enhancement (ANCE) technique in increasing the sensitivity of breast cancer diagnosis. Seventy-eight screen-film mammograms of 21 difficult cases (14 benign and seven malignant), 222 screen-film mammograms of 28 interval cancer patients and six benign control cases were digitized with a high-resolution of about 4096 x 2048 x 10-bit pixels and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 27 publications
0
29
0
4
Order By: Relevance
“…Rangayyan et al [30,38] investigated the performance of their ANCE algorithm in increasing the sensitivity of breast cancer diagnosis by using ROC analysis and McNemar's tests [28]. A set of 78 screen-film mammograms of 21 difficult cases (14 malignant and seven benign) and another set of 222 screen-film mammograms of 28 interval cancer patients and six benign control cases were digitized with a resolution of about 4096 Â 2048 Â 10-bit pixels, and subsequently processed with the ANCE algorithm.…”
Section: Image Enhancementmentioning
confidence: 98%
See 1 more Smart Citation
“…Rangayyan et al [30,38] investigated the performance of their ANCE algorithm in increasing the sensitivity of breast cancer diagnosis by using ROC analysis and McNemar's tests [28]. A set of 78 screen-film mammograms of 21 difficult cases (14 malignant and seven benign) and another set of 222 screen-film mammograms of 28 interval cancer patients and six benign control cases were digitized with a resolution of about 4096 Â 2048 Â 10-bit pixels, and subsequently processed with the ANCE algorithm.…”
Section: Image Enhancementmentioning
confidence: 98%
“…The enhancement of mammographic images could improve the accuracy of detection of early signs of breast cancer. For reviews on image enhancement in mammography, see Rangayyan [28], Morrow et al [29], and Rangayyan et al [30].…”
Section: Image Enhancementmentioning
confidence: 99%
“…The objective of this procedure is to increase the contrast between mammogram structures and their background, while providing a relatively uniform intensity to all of the structures. Previous studies [17,21,23,26] have demonstrated the benefits of applying a contrast enhancement processing driven by the local characteristics of the mammograms. In our contrast enhancement routine, statistical measures of the pixel intensities in local neighborhoods are employed to automatically set the parameters of the transform applied to each pixel.…”
Section: Mammogram Enhancementmentioning
confidence: 99%
“…While the latter group enhance the contrast without measuring the contrast itself, the former one use a local definition of the contrast information which is then modified by a mapping function to generate the enhanced image. Several studies have been devoted to contrast enhancement on mammographic images [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] using both direct and indirect enhancement methods. Techniques used for that purpose reveal six broad categories: unsharp masking [1,2] histogram equalization [3,4] region based or adaptive neighbourhood contrast enhancement [5][6][7][8][9] wavelet enhancement [10,11], fuzzy modelling [12,13] and spatial filtering [14,15].…”
Section: Introductionmentioning
confidence: 99%